Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan - Sinta Herlini Putri (Yayasan Insani Mandiri Santani, 2020)
This study aims to determine: (1) The effect of job discipline on employee performance at The Madeline Hotel Bengkulu, (2) The effect of the job environment on employee performance on The Madeline Hotel Bengkulu, (3) The effect of job discipline and job environment partially and simultaneously on employee performance at The Madeline Hotel Bengkulu. This study is a type of research with a Quantitative Descriptive method, which the research compares the results of data collection and proves with numbers in a number of population through sample that are considered feasible to study. This study categorized into survey research, where the research instrument is a questionnaire. The sample in this study is the entire population of employees of The Madeline Hotel Bengkulu, and the number is 40 people. The validity test used Corrected Item Total Correlation Statement, Cronbach's Alpha reliability test, while data analysis uses multiple linear regression analysis. The results of thestudy showed that: (1) Job Discipline has an effect on Employee Performance. This can be seen in the t- test that states a value of t-hit > t (α / 2) 3,545 > 2,026) and (sig α = 0.003 < 0.05), then H1 in this study can be accepted, (2) Job Environment has an effect on Employee performance. This can be seen in the t- test which states that the value of t-hit > t_ (α / 2) (4,528 > 2,026) and (sig α = 0,000 < 0.05), then H2 in this study is acceptable, (3) Job Discipline X1 and Job Environment X2 have an effect on Employee Performance (Y), this can be seen in the F- test which states the value of F-count > F-table, i.e. (51,651 > 1.97) and (sig α = 0,000 <0.050), thus it can be concludeed that H3 accepted that means simultaneously the Job Discipline variabel (X1) and Job Environment (X2) have a significant effect on Employee Performance (Y) at The Medeline Hotel Bengkulu.